The index of clothing for assessing tourism climate comfort: Development and application - Liu, Qun; Lin, Lan; Deng, Haijun; Zheng, Yingling; Hu, Zengyun (Frontiers in Environmental Science, 2023)
Climate comfort is a significant factor in analyzing the effects of climate change on tourism, and considerable research has used multidimensional climate indices to evaluate climate comfort. In particular, the index of clothing (ICL) is recognized as one of the most popular climate indices and has been widely applied in many studies. While few studies focused on the calculation method of the ICL model’s surface solar radiation (Ract), the computed value was greater than that observed at ground stations. Thus, this study tried to improve solar radiation energy calculation on the earth's surface in the ICL model with the method recommended by the International Food and Agriculture Organization (FAO), and then validated the new model based on the meteorological data of 31 provincial capitals in mainland China during 1980-2019. Results showed that: (1) The value of Ract calculated by the International Food and Agriculture Organization (FAO) method was close to the site observations (Pbais <15%), and was suggested to be used in enhancing the estimate approach for Ract in the ICL; (2) Different from the original ICL, ICL-new is significantly more effective in evaluating climate comfort in middle and low latitude regions; (3) Climate change had a considerable influence on the climate comfort of cities in mainland China. Since 1980, the climate comfort of cities in eastern China had increased in spring, while that of cities in western China had declined, and most cities had a decreasing trend in summer. Finally, our findings revealed that ICL-new can realistically and precisely depicts the actual scenario than the original ICL, and it is more suitable to provide scientific impact assessment and tourism management for government agencies and destination management.